Armeniaspirols inhibit the AAA+ proteases ClpXP and ClpYQ leading to cell division arrest in Gram-positive bacteria. Issue 12 (16th December 2021) - Labana, Puneet; Dornan, Mark H.; Lafrenière, Matthew; Czarny, Tomasz L.; Brown, Eric D.; Pezacki, John P.; Boddy, Christopher N.
Summary: Multi-drug-resistant bacteria present an urgent threat to modern medicine, creating a desperate need for antibiotics with new modes of action. As natural products remain an unsurpassed source for clinically viable antibiotic compounds, we investigate the mechanism of action of armeniaspirol. The armeniaspirols are a structurally unique class of Gram-positive antibiotic discovered from Streptomyces armeniacus for which resistance cannot be readily obtained. We show that armeniaspirol inhibits the ATP-dependent proteases ClpXP and ClpYQ in vitro and in the model Gram-positive Bacillus subtilis . This inhibition dysregulates the divisome and elongasome supported by an upregulation of key proteins FtsZ, DivIVA, and MreB inducing cell division arrest. The inhibition of ClpXP and ClpYQ to dysregulate cell division represents a unique antibiotic mechanism of action and armeniaspirol is the only known natural product inhibitor of the coveted anti-virulence target ClpP. Thus, armeniaspirol possesses a promising lead scaffold for antibiotic development with unique pharmacology. Graphical abstract: Highlights: Inhibitor capture with armeniaspirol probe shows AAA+ proteases as direct targets Armeniaspirol inhibits recombinant purified ClpXP and ClpYQ AAA+ proteases Dimethyl labeling quantitative proteomics proves protease inhibition in B. subtilis AAA+ protease inhibition disrupts divisome and elongasome complexes Abstract : The discovery of new antibiotic mechanisms of action is essential to overcome antimicrobial resistance. Labana et al. uncover the unique pharmacology of the natural product Gram-positive antibiotic armeniaspirol using proteomics-, biochemical-, and microscopy-based methods. They show that armeniaspirol inhibits the AAA+ proteases ClpXP and ClpYQ in Bacillus subtilis, arresting cell division.